A Preliminary Survey of the Fertility Status of Soils in Ondo State under Traditional Cultivation - Adepetu, J. A.; Adebayo, A. A.; Aduayi, E. A.; Alofe, C. O. (Faculty of Agriculture, University of Ife, 2015)
Surface and subsoil samples, as well as maize leaf samples were collected from local fields at about ten kilometers intervals along the major and minor highways across Ondo state in 1977. The samples were subsequently processed and analysed for various components in the laboratory. The surface 0-15cm soil samples showed a mean of 23; 7pp NO3 -N, 13.6ppm avail. P, 119.4ppm exch. K, 1168 ppm exch. Ca, 98.2 ppm exch. Mg, and Na-EDTA-extractable trace elements in the amount 131.9, 9.0, 319 and 1.3ppm of Fe. Zn, Mn, and Cu respectively. About 93% of the samples had a pH value between 5 and 7, while the soils had a mean 0.M content of 1.9% and C.E.C. of 11.4 meq/100g soil. About 77% of samples had a base saturation exceeding 50%. The values of these parameters generally decline down the soil profile to the 90cm depth studied.